Transport of the fluorescent organic cation 4-(4-(dimethylamino)styryl)-N-methylpyridinium iodide (ASP+) in human respiratory epithelial cells - SALOMON, JOHANNA; EHRHARDT, CARSTEN; BUCKLEY, STEPHEN (My University, 2012)
Organic cation/carnitine transporters (OCT/N) mediate uptake of positively charged molecules. Their role in lung epithelium, however, is not well understood. OCT/N expression and activity was studied in cell lines of human alveolar (A549), bronchial (16HBE14o- and Calu-3) and intestinal (Caco-2) epithelium. Protein levels were largely comparable for all OCT/Ns in the respiratory epithelial cell lines studied, however, OCT2 was exclusively observed in A549 cells. OCT1 and -2 were present at significantly higher levels in Caco-2 cells, compared with the pulmonary epithelial cell types. OCTN1 and -2 were also more abundant in Caco-2. Only OCT3 was expressed evenly across all cell lines investigated. Uptake of 4-(4-(dimethylamino)styryl)-N-methylpyridinium iodide (ASP+) was dependent on concentration, temperature, membrane potential and pH. In 16HBE14o-, Calu-3 and Caco-2 monolayers substrate saturation of ASP+ uptake was not reached. Alveolar A549 cells showed saturable ASP+ uptake via two transporter sites with Km values of 12.5?4.0 ?M and 456.9?164.5 ?M, respectively. This uptake was sensitive to organic cations, but insensitive to carnitine and lysine. We conclude that uptake of organic cations is facilitated by distinct pathways in different regions of lung mucosa. Luminally localised OCT2 appears to be exclusively involved in the alveolar epithelium, whereas basolateral localised OCT3 might play a role in alveolar as well as in bronchial epithelial cells.
PUBLISHED
Keywords: Pharmacology; Organic cation transporters; Bronchial epithelium; Alveolar epithelium; Pulmonary drug disposition; Inhalation biopharmaceutics; Immunology, Inflammation & Infection